Correlation of P Wave Dispersion and Quality of Life of Heart Failure Due to Coronary Heart Disease Patient in Haji Adam Malik General Hospital - Hillary, Lastri; Nasution, Ali Nafiah; Lubis, Anggia Chairuddin (Journal of Society Medicine, 2024)
Introduction: P wave dispersion is a more sensitive cardiovascular marker which obtained by the ECG to elaborate structural and electrophysiological abnormalities in patients. This study aims to elucidate P wave dispersion prevalence in heart failure due to coronary heart disease patients and the correlation with their quality of life. Method: This analytical cross-sectional study is done in RSUP Haji Adam Malik in 133 patients with heart failure from May to June 2023. Patients had undergone clinical evaluation, physical examination, 12-lead electrocardiography (ECG), and then were given the MLFHQ to assess the quality of their lives. Data were analyzed using fischer-exact test, with p value less than 0.05 considered to be significant. Results: From the total of 133 sample of patients, there were 55 (43.2%) patients with positive p wave dispersion, among them 2 had low quality of life, 25 had moderate quality of life, and 28 had good quality of life. With mean of PWD is 27.9±15.1 ms. The group of patient with negative p wave dispersion 78 had moderate and good quality of life. P value is less than 0.01. It’s concluded that there was a positive correlation between p wave dispersion and quality of life of heart failure patients in Haji Adam Malik general hospital Conclusion: There is positive correlation between p wave dispersion and quality of life of heart failure due to coronary heart disease patients in Haji Adam Malik general hospital.